Bank Capitalisation and Stock Market Liquidity: Assessing the Evidence - Soliman, Alaa M.; Obi, Joseph (Scientific Research, 2017)
This paper provides both theoretical and empirical evidence for assessing the relationship between bank capitalisation and stock market liquidity. It estimates a bivariate VAR-GARCH (1.1) model to examine the linkage between bank capitalisation and stock market liquidity in Nigeria using annual data covering the period from 1986 to 2014. The findings of this paper show that bank capitalisation enables banks to give out more loans to the public and this increase in lending has a positive impact on stock market liquidity growth. The findings support the view that capitalised banks are well equipped to absorb and diversify risk, give out more loans, improve liquidity in the economy and improve stock market performance.
Keywords: Bank Capitalisation; Stock Market; Nigeria; VAR